Mechanism and kinetics of epoxide ring-opening with carboxylic acids catalyzed by the corresponding carboxylates. (12th October 2021) - Yan, Zifei; Ma, Zeyu; Deng, Jian; Luo, Guangsheng
Graphical abstract: Highlights: The nucleophilicity of carboxylate catalyst determines its catalytic activity. Strong polar solvent promotes catalyst dissociation and improve reactivity. Larger cation radius weakens electrostatic effects and enhance nucleophilicity. Branched chains of anion improve reactivity by raising electrostatic potential. Abstract: The ring-opening reactions of epoxides with carboxylic acids have great applications in the coating and polymer industry. However, the systematical study on the structure-activity relation of catalysts is still scarce. In this work, the carboxylate catalysts were directly prepared rather than using the traditional catalysts like amines or quaternary ammonium salts, thus removing the induction period and making the kinetic results more accurate and rigorous. The reaction orders of reactants and catalyst were obtained by kinetic experiments, and based on that, the kinetic equation and mechanism were put forward. The influences of solvent environment, as well as the structure and properties of catalysts on their activity were further studied. It was found that the alkalinity of the carboxylate ions and the electrostatic interaction are the key factors to affect the nucleophilicity of catalysts. Generally, the nucleophilicity is enhanced with the increase of cation radius and anion branches.